rRNA biogenesis regulates mouse 2C-like state by 3D structure reorganization of peri-nucleolar heterochromatin - Hua Yu (Nature Portfolio, 2021)
The role of the nucleolus in cell fate is not well known. Here the authors show nucleolar integrity maintained by rRNA-mediated liquid-liquid phase separation and 3D chromatin structure of perinucleolar heterochromatin regulates the fate transition of mouse embryonic stem cells to 2 cell-stage embryo-like cells, and that rRNA biogenesis regulates the 2-cell-to-4-cell transition of development.